Maternal use of fertility drugs and risk of cancer in children—A nationwide population‐based cohort study in Denmark. Issue 8 (6th October 2014) - Hargreave, Marie; Jensen, Allan; Nielsen, Thor Schütt Svane; Colov, Emilie Palmgren; Andersen, Klaus Kaae; Pinborg, Anja; Kjaer, Susanne Krüger
<x xml:space="preserve">Abstract</x> Large population‐based studies are needed to examine the effect of maternal use of fertility drugs on the risk of cancer in children, while taking into account the effect of the underlying infertility. A cohort of 123, 322 children born in Denmark between 1964 and 2006 to 68, 255 women who had been evaluated for infertility was established. We used a case–cohort design and calculated hazard ratios (HRs) for cancer in childhood (0–19 years) and in young adulthood (20–29 years) associated with maternal use of six groups of fertility drugs (clomiphene, gonadotropins [i.e., human menopausal gonadotropins and follicle‐stimulating hormone], gonadotropin‐releasing hormone analogs, human chorionic gonadotropins, progesterone and other fertility drugs). We found no statistically significant association between maternal use of fertility drugs and risk for overall cancer in childhood or young adulthood. However, with regard to specific cancers in childhood, our results showed that maternal use of progesterone before childbirth markedly increased the risks of their offspring for acute lymphocytic leukemia (any use: HR, 4.95; 95% CI, 1.69–14.54; ≥ three cycles of use: HR, 9.96; 95% CI, 2.63–37.77) and for sympathetic nervous system tumors (any use: HR, 5.79; 95% CI, 1.23–27.24; ≥ three cycles of use: HR, 8.51; 95% CI, 1.72–42.19). These findings show that maternal use of progesterone may increase the risk for specific cancers in the offspring. Additional large epidemiological studies are urgently needed to confirm our finding.